Epigean tenebrionids (coleoptera: Tenebrionidae) from the choros archipelago (Coquimbo Region, Chile) - Alfaro, Fermín (2009)
Using pitfall traps, we studied the taxonomic diversity of epigean tenebrionids in the Choros Archipelago, formed by the Choros, Damas and Gaviota Islands, which are part of the Pinguino de Humboldt National Reserve. We identified fourteen species arranged in eight genera and six tribes, of which seven species were common to the archipelago. Five genera are reported for the first time as occurring in insular habitat islands: Psectrascelis Solier, Ento,noehilus Solier, Diastoleus Solier, Scot obiu.r Germar, and Thinobatis Eschscholtz, Gvriosonws granulipennis Pizarro-Araya and Flores is recorded as endemic to the Choros Island.